2011
DOI: 10.1109/tmi.2011.2139222
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Articular Cartilage Using Multiphoton Microscopy: Input for Biomechanical Modeling

Abstract: The 3-D morphology of chicken articular cartilage was quantified using multiphoton microscopy (MPM) for use in continuum-mechanical modeling. To motivate this morphological study we propose aspects of a new, 3-D finite strain constitutive model for articular cartilage focusing on the essential load-bearing morphology: an inhomogeneous, poro-(visco)elastic solid matrix reinforced by an anisotropic, (visco)elastic dispersed fiber fabric which is saturated by an incompressible fluid residing in strain-dependent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 45 publications
1
44
0
Order By: Relevance
“…This type of dispersed fiber distribution has been found in human arterial tissues [1,5], the myocardium [9,10], corneas [11,12], articular cartilage [13] and other tissues. Currently, there exist two main approaches for representing fiber dispersion in a constitutive equation: direct incorporation in a strain-energy function through a probability density function (PDF) [14] or by using a generalized structure tensor [15].…”
Section: Introductionmentioning
confidence: 62%
“…This type of dispersed fiber distribution has been found in human arterial tissues [1,5], the myocardium [9,10], corneas [11,12], articular cartilage [13] and other tissues. Currently, there exist two main approaches for representing fiber dispersion in a constitutive equation: direct incorporation in a strain-energy function through a probability density function (PDF) [14] or by using a generalized structure tensor [15].…”
Section: Introductionmentioning
confidence: 62%
“…Specifically, in human arterial walls the collagen fibers are not perfectly aligned but are dispersed around a mean direction. Such a fiber dispersion has been observed in, for example, human arterial walls [1][2][3][4][5], the myocardium [6,7], corneas [8,9] and articular cartilage [10]. In particular, recent extensive experimental results [4] have shown that the collagen fiber dispersion in each of the layers of (healthy) human thoracic and abdominal aortas and iliac arteries is non-symmetric, in contrast to the rotationally symmetric fiber dispersion assumed in previous studies; see, for example, [11].…”
Section: Introductionmentioning
confidence: 78%
“…Recent work [7] has revealed that, while helical fibre structures are present in human elastic arteries, in more muscular arteries (as for the murine basilar artery) and veins (such as the porcine jugular vein) a transition from the helical arrangement to two nearly orthogonal fibre families aligned in the circumferential and axial directions can be observed, and it is suggested that this is to ensure optimal efficiency of the vasculature. Observations of dispersion for other tissues, including the myocardium, corneas and articular cartilage, can be found in [8,9], [10,11] and [12], respectively.…”
Section: Introductionmentioning
confidence: 99%